MAJOR DIFFICULTIES OF TRANSLATING THE TITLES OF ENGLISH FILMS INTO RUSSIAN - Safarova Dilarom Abdukadirovna (Western European Studies, 2026)
The translation of film titles represents a complex area of audiovisual translation, combining linguistic, cultural, pragmatic, and marketing considerations. English movie titles, when translated into Russian, often undergo significant transformations, which may result in semantic shifts, loss of stylistic effect, or cultural reinterpretation. This article examines the main problems encountered in translating English film titles into Russian, identifying main translation strategies, and analyzes the factors influencing translators’ decisions. Special attention is paid to lexical meaning, cultural references, pragmatic adaptation, and commercial motivations
Keywords: film title translation; English–Russian translation; lexicology